(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
Andr Neher writes in his book Ils ont refait leur me: Genesis and Exodus meet at the crossroads of Who? and Where?. The problem of Jewish identity, in fact, cannot be addressed starting from the question: Who are you?. The Jew is related to the first question posed by God to Adam in Genesis: Where are you?. In the Hebrew problematic, it is of the same identity as God. Instead, Pharaoh, urged by Moses for the sake of the Jews freedom, asks: Who is God?. As in: I do not know Him. Neher explains: You cannot ask: Who is God?. That would be denying it. All you can ask is: Where is God?.